Reward as Motivational Strategy for Productivity in Private Schools in Nigeria: The Case of Kevad International Academy, Koroduma Karu, Nasarawa State - Akor Abbah Innocent; Akor Onyeche Linda (Researchparks Publishing, 2021)
This study focused on the effect of reward as a strategy for motivating organizational staff to achieve positive work attitude and high productivity. Kevad International Academy, a private primary and secondary institution, located in Karu Local Government Area of Nasarawa State, was used as case study. The entire staff population of 24 was selected as sample for data collection and analysis, using the Chi-Square statistical tool. The null hypothesis that Reward (sub-variable of motivation) has no significant impact on staff productivity in Kevad International Academy was tested using the Chi-square statistical tool. The result showed that reward as a motivational strategy has highly significant effect on organizational productivity. It was concluded that workers tend to perform more effectively if their wages are related to performance which is not based on personal bias or prejudice, but on objective evaluation of an employee’s merit. The paper recommends that the results of annual personnel evaluation should be made available to staff for discussion and possible adjustment.